Siak Palace Inspiration for Gala Evening Party Dressmaking - Irlanita Indah Pratiwi; Sugiyem Sugiyem (Jurusan Pendidikan Kesejahteraan Keluarga, Fakultas Teknik, Universitas Negeri Semarang, 2023)
Inspiration for dressmaking can come from various sources, such as nature and the surrounding environment, culture and traditions, film, music, and art; textiles and fabrics; and architecture and interior design. Indonesia has many heritage buildings that can be a source of inspiration in gala evening party dressmaking, one of which is the Siak Palace in Riau. Siak Palace is one of the heritage buildings that can be a source of inspiration in fashion creation. Some elements of Siak Palace that can be used as inspiration in designing clothing include colors, ornamental motifs, shapes, textures, and traditional Malay clothing. In evening party dressmaking, inspiration from Siak Palace can be taken from the forms of decoration found in buildings and furniture in the palace. In addition, the dominant colors in Siak Palace, such as red, gold, and green, can be a color choice for elegant and magnificent party clothes. The shapes of objects in Siak Palace, such as jewelry, wood carvings, and wicker, can also inspire details on clothing. By combining elements from Siak Palace with modern fashion designs, it can produce unique and stunning party clothes. Gala evening party dressmaking with silhouette A with elements of white and gold, bustier with a princess line, 1/2 circle skirt that has a cleavage on the front, a long shawl on each sleeve, cone-shaped padding variations, using wrap buttons and Japanese zipper, decoration in some parts is one embodiment of the creation of party fashion with the source of the idea of the Siak palace. By taking inspiration from Siak Palace, people can appreciate Indonesian culture and history. In this case, party fashion is not only an ordinary outfit but also a medium to introduce the richness of Indonesian culture and history to the world.